2009
DOI: 10.4161/auto.5.1.7181
|View full text |Cite
|
Sign up to set email alerts
|

Measuring piecemeal microautophagy of the nucleus inSaccharomyces cerevisiae

Abstract: Piecemeal microautophagy of the nucleus (PMN) selectively removes and degrades small fragments of the Saccharomyces cerevisiae nucleus. Inter-organelle contact sites called nucleus-vacuole (NV) junctions determine the selectivity of PMN by establishing a platform for the biogenesis of PMN blebs and vesicles. PMN structures can be observed by fluorescence microscopy using GFP-tagged reporters; however, this approach is best supported with quantitative immunoblot assays of PMN-specific cargo degradation. Togethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 12 publications
0
41
0
Order By: Relevance
“…PMN is classified as microautophagy because the delivery of the nuclear bleb to the vacuole occurs by direct invagination and scission of the vacuole membrane, without involvement of autophagosome structures. Notably, components of the homotypic vacuole fusion machinery that are required for macroautophagy processes are not needed, emphasizing that PMN is a microautophagy process (Krick et al, 2008;Krick et al, 2009;Millen et al, 2009). As yeast has a closed mitosis (i.e.…”
Section: Piecemeal Microautophagy Of the Nucleusmentioning
confidence: 99%
See 1 more Smart Citation
“…PMN is classified as microautophagy because the delivery of the nuclear bleb to the vacuole occurs by direct invagination and scission of the vacuole membrane, without involvement of autophagosome structures. Notably, components of the homotypic vacuole fusion machinery that are required for macroautophagy processes are not needed, emphasizing that PMN is a microautophagy process (Krick et al, 2008;Krick et al, 2009;Millen et al, 2009). As yeast has a closed mitosis (i.e.…”
Section: Piecemeal Microautophagy Of the Nucleusmentioning
confidence: 99%
“…The cargo that is sequestered by PMN includes nonessential nuclear components, such as the granular nucleolus that is enriched in preribosomes, as well as the surrounding portion of nuclear membranes (Roberts et al, 2003). Nucleus-derived components, such as bulk chromatin, nuclear pore complexes and spindle pole bodies are excluded from PMN vesicles (Roberts et al, 2003;Krick et al, 2009;Millen et al, 2009).…”
Section: Piecemeal Microautophagy Of the Nucleusmentioning
confidence: 99%
“…Therefore we tested weather Nvj2p was also required for PMN. Previous studies have shown that rapamycin induces PMN (Dawaliby and Mayer, 2010;Millen et al, 2009). To assess PMN induction we monitored the internalization of the nucleoplasm protein Pus1-GFP in the vacuole after rapamycin addition.…”
Section: Nvj2p Is Not Required For Nvj Formation or Piecemeal Microaumentioning
confidence: 99%
“…65 Nuclear components targeted for PMN include granular nucleolus enriched in pre-ribosomes and nuclear envelope, nuclear pore complexes or spindle pole bodies. 66,67 PMN involves the core Atg proteins involved in macroautophagy and microautophagy, such as Atg4, 5, 7 and 12, as well as macroautophagy-specific proteins such as Atg17, 29 and 31. 64 In mammalian cells, autophagy can degrade nuclear components, thereby contributing to the maintenance of nuclear function and integrity.…”
Section: Nucleophagy As a Way To Eliminate Injured Dnamentioning
confidence: 99%